Penanaman nilai sosial pada pembelajaran muatan IPS kelas V sekolah dasar - Rahmawati, Fitri; Istiyati, Siti; Kamsiyati, Siti (Universitas Sebelas Maret, 2023)
The descriptive qualitative research conducted aims to describe the cultivation of social values in social studies learning grade V elementary school. The subjects of this study were students and teachers of the VA class at SD Negeri Mangkubumen Kidul. Research data obtained from interviews, observations and questionnaires. Validity in this study used triangulation techniques and the analysis of Miles-Huberman model. The outcomes of this research show that teachers instill social values in several ways; 1) Instillation of social values through learning methods is lecture methods, giving concrete questions, questions and answers, reward-punishment, assignment methods;2) Planting social values through example and habituation, exemplary through arriving on time, welcoming students a friendly way, habituation tenable with routine activities such as praying, cleaning the table and spontaneous activities such as asking students for help;3) Verbal instillation of social values through motivation, reprimand and advice. motivation is given in by praise, reprimand and advice is given when students show unkind behavior such as arriving late, not collecting assignments, making rowdy in class. In this way, teachers implicitly instill social values in students, so that students can demonstrate behaviors that reflect social values and social values embedded in students that are integrated through learning activities.